COMPARATIVE ANALYSIS OF THE CONTENT IN LYMPH OF HORMONES DRAWING IN PATHOGENESIS OF BREAST CANCER IN RATS WISTAR - A. P. Lykov; M. A. Bondarenko; O. V. Poveshchenko; A. V. Kabakov; T. V. Rayter; O. V. Kazakov; D. N. Strunkin; A. F. Poveshchenko; V. I. Konenkov (Сибирский онкологический журнал)
The aim of the research was to study the levels of hormones involved in the pathogenesis of BC in the lymph of the thoracic duct. Methods. BC induced by the introduction of n-methyl-N-nitrosourea rats of Wistar breed. The animals underwent only surgery chemotherapy (cyclophosphamide, methotrexate, 5-fluorouracil). In some animals combined surgery followed by a course of chemotherapy, and in some animals advanced therapy fragmented DNA. In the lymph examined the contents of the follicle-stimulating hormone (FSH), prolactin, luteinizing hormone (LH), estradiol (E2 ) and thyroglobulin (TG). Results. It is shown that surgical removal of tumors in the mammary gland leads to lower levels in the lymph LH and E2 . The combination of surgery with a course of chemotherapy leads to lower levels in the lymph FSH. Chemotherapy without surgical removal of tumors in the mammary gland leads to a decrease in the concentration of E2 in the lymph. Conclusion. The concentration of sex hormones and thyroglobulin in the lymph of the thoracic duct in breast cancer in rats depends on the type of treatment.